EKSPLORASI STRATEGI REGULASI EMOSI REMAJA MUSLIM MELALUI AKTIVITAS KEAGAMAAN DI MUSLIMEEN SUKSA SCHOOL: Pendidikan berlatar keagamaan - Nokia Aisy; Nanik Kholifah (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT Adolescents aged 13–16 years are in a complex developmental phase characterized by biological, cognitive, and social changes that often lead to academic and social pressures, particularly in religion-based educational environments that integrate academic demands with religious activities. This study aims to understand adolescents’ subjective experiences in regulating emotions when facing academic and social pressures in a religion-based educational institution. The study employed a qualitative descriptive approach using observation, in-depth interviews, and documentation techniques involving adolescents at Muslimmeen Suksa School, Southern Thailand. The data were analyzed using thematic analysis to identify emotional experiences and emotion regulation strategies used by students. The findings revealed that formal and nonformal religious activities, such as religious learning, Qur’an memorization, and routine worship, played an important role in reducing stress, improving self-control, and fostering emotional calmness among adolescents. The emotion regulation that developed was integrative in nature through the combination of spiritual strategies and nonreligious personal coping strategies. This study concludes that the integration of academic and religious education plays an important role in supporting the emotional balance of Muslim adolescents and can serve as a basis for developing educational and emotional assistance programs in integrated educational environments. ABSTRAK Remaja usia 13–16 tahun berada pada fase perkembangan yang kompleks dengan berbagai perubahan biologis, kognitif, dan sosial yang sering kali memunculkan tekanan akademik maupun sosial, terutama dalam lingkungan pendidikan berbasis agama yang memadukan tuntutan akademik dan aktivitas keagamaan. Penelitian ini bertujuan untuk memahami pengalaman subjektif remaja dalam meregulasi emosi ketika menghadapi tekanan akademik dan sosial di lembaga pendidikan berbasis agama. Penelitian menggunakan pendekatan deskriptif kualitatif dengan teknik pengumpulan data berupa observasi, wawancara mendalam, dan dokumentasi terhadap remaja di Muslimmeen Suksa School, Thailand Selatan. Data dianalisis menggunakan analisis tematik untuk mengidentifikasi pengalaman emosional dan strategi regulasi emosi yang digunakan peserta didik. Hasil penelitian menunjukkan bahwa aktivitas keagamaan formal dan nonformal, seperti pembelajaran agama, hafalan Al-Qur’an, dan ibadah rutin, berperan dalam membantu remaja mengurangi stres, meningkatkan kontrol diri, serta menciptakan ketenangan emosional. Regulasi emosi yang berkembang bersifat integratif melalui perpaduan strategi spiritual dan coping personal nonreligius. Penelitian ini menyimpulkan bahwa integrasi pendidikan akademik dan keagamaan memiliki peran penting dalam mendukung keseimbangan emosi remaja Muslim serta dapat menjadi dasar pengembangan program pendidikan dan pendampingan emosional di lingkungan pendidikan terpadu.